2021
DOI: 10.3389/fnsys.2021.712664
|View full text |Cite
|
Sign up to set email alerts
|

Driving Oscillatory Dynamics: Neuromodulation for Recovery After Stroke

Abstract: Stroke is a leading cause of death and disability worldwide, with limited treatments being available. However, advances in optic methods in neuroscience are providing new insights into the damaged brain and potential avenues for recovery. Direct brain stimulation has revealed close associations between mental states and neuroprotective processes in health and disease, and activity-dependent calcium indicators are being used to decode brain dynamics to understand the mechanisms underlying these associations. Ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 134 publications
(151 reference statements)
0
10
0
Order By: Relevance
“…[226][227][228][229] Hence, deeppenetrating TUS with high resolution qualify as an excellent neuromodulation tool for elaborating the role of subcortical structures in post-stroke recovery and potentially for improvement of the motor recovery process by modulating neural network dynamics. 230 Several studies have shown both exhibitory effects in animals [231][232][233] and humans 92,234,235 and inhibitory effects in animals 87,119,236 and humans 107,211,216 for TUS in deeper brain regions. A first human study applying TUS for neuromodulation to thalamus, showed physiological and behavioral effects targeting the unilateral thalamus containing the ventroposterior lateral (VPL) nucleus using a combined approach with TMS and TUS with a singleelement transducer using 500 ms burst, 0.5 MHz center frequency and ISPPA of 7.03 W/cm 2 .…”
Section: Spinal Cord Stimulation (Scs)mentioning
confidence: 99%
See 1 more Smart Citation
“…[226][227][228][229] Hence, deeppenetrating TUS with high resolution qualify as an excellent neuromodulation tool for elaborating the role of subcortical structures in post-stroke recovery and potentially for improvement of the motor recovery process by modulating neural network dynamics. 230 Several studies have shown both exhibitory effects in animals [231][232][233] and humans 92,234,235 and inhibitory effects in animals 87,119,236 and humans 107,211,216 for TUS in deeper brain regions. A first human study applying TUS for neuromodulation to thalamus, showed physiological and behavioral effects targeting the unilateral thalamus containing the ventroposterior lateral (VPL) nucleus using a combined approach with TMS and TUS with a singleelement transducer using 500 ms burst, 0.5 MHz center frequency and ISPPA of 7.03 W/cm 2 .…”
Section: Spinal Cord Stimulation (Scs)mentioning
confidence: 99%
“…To determine and understand appropriate parameters for clinical feasibility and efficacy, for paving the way of a novel non-invasive deep brain stimulation method, more research must be conducted Neural oscillations are a key factor to modulate pathological progress and recovery in stroke. 230 Furthermore, non-invasively evoked neural oscillation changes have recently been discussed as potential, promising therapeutic option to restore intrinsic homeostasis to support the neurorecovery process following a stroke. 230 As the oscillatory behavior of neural populations change over the reorganization course following a stroke, several approaches for phase-dependent neuromodulation have been proposed.…”
Section: Spinal Cord Stimulation (Scs)mentioning
confidence: 99%
“…DBS modulates neural circuits and has been used to treat multiple neurological disorders [36][37][38][39][40][41] . However, using high-frequency stimulation (HFS) to lower the T core for brain protection has not been attempted before 39,40 .…”
Section: Dbs Of Mpn Evokes Deep Hypothermiamentioning
confidence: 99%
“…Nevertheless, more than half of stroke victims maintain severe long-term disability, and more than two-thirds of survivors experience lingering paresis of the upper extremity despite intensive rehabilitation, warranting additional strategies to enhance the effects of physical rehabilitation and improve long-term outcomes (Go et al, 2014). Neuromodulation is an important technique with potential to increase the contributions of motor regions to recovery (Elias et al, 2018;Storch et al, 2021;Ting et al, 2021). Better understanding of physiological changes in networks that contribute to poststroke plasticity and rehabilitation is key to identifying novel, more suitable neuromodulation targets and better paradigms of stimulation.…”
Section: Introductionmentioning
confidence: 99%